Light drinking in pregnancy and mid-childhood mental health and learning outcomes - Sayal, Kapil; Draper, Elizabeth S.; Fraser, Robert; Barrow, Margaret; Smith, George Davey; Gray, Ron (BMJ Publishing Group, 2013)
OBJECTIVE: To investigate whether light drinking in pregnancy is associated with adverse child mental health and academic outcomes. DESIGN: Using data from the prospective, population-based Avon Longitudinal Study of Parents and Children (ALSPAC), we investigated the associations between light drinking in pregnancy (<1 glass per week in the first trimester) and child mental health (using both parent and teacher rated Strengths and Difficulties Questionnaires (SDQs)) and academic outcomes based on Key Stage 2 examination results at age 11 years. PARTICIPANTS: 11-year-old children from ALSPAC with parent (n=6587) and teacher (n=6393) completed SDQs and data from Key Stage 2 examination results (n=10 558). RESULTS: 39% of women had consumed <1 glass per week and 16% ≥1 glass per week of alcohol during the first trimester (45% abstaining). After adjustment, relative to abstainers, there was no effect of light drinking on teacher-rated SDQ scores or examination results. In girls, although there was a suggestion of worse outcomes (adjusted regression coefficient=0.38; 95% CI 0.01 to 0.74) on the parent-rated total SDQ score in those exposed to light drinking compared to abstainers, no dose-response relationship was evident. CONCLUSIONS: Although the pattern of findings involving parent ratings for girls exposed to light drinking is consistent with earlier findings from this cohort, the overall lack of any adverse effects of light drinking is similar to findings from other recent cohort studies. Light drinking in pregnancy does not appear to be associated with clinically important adverse effects for mental health and academic outcomes at the age of 11 years.